Investor Status Weakens the Application of Electronic Transaction Fraud Liability : Status Investor Melemahkan Penerapan Pasal Penipuan Transaksi Elektronik - Muhammad Vicry; R. Rahaditya (Indonesian Journal of Law and Economics Review, 2026)
General Background: The rapid development of information technology has expanded digital investment activities through electronic platforms, including Telegram, while simultaneously increasing the occurrence of fraudulent investment schemes. Specific Background: Indonesian law criminalizes the dissemination of false and misleading information that causes consumer losses in electronic transactions under Article 28(1) of the Electronic Information and Transactions Law. Knowledge Gap: Despite judicial findings regarding misleading information and financial losses, the legal qualification of victims as consumers in fraudulent digital investment cases remains insufficiently examined. Aims: This study analyzes the application of the element of “consumer losses in electronic transactions” in Decision Number 534/Pid.Sus/2023/PN.Jkt.Brt and examines whether victims of the Telegram-based “LAMBE CAPITAL” investment scheme qualify as consumers under Article 28(1) of the Electronic Information and Transactions Law. Results: Using normative legal research with statutory and case approaches, the study finds that the court successfully established the dissemination of false and misleading information through electronic media and the existence of victim losses. However, the judicial reasoning did not comprehensively address the legal status of the victims. The factual relationship between the parties reflected an investment arrangement involving capital placement for profit rather than a consumer transaction involving end-users of goods or services. Novelty: This study provides a focused legal assessment of the distinction between investor and consumer status in applying Article 28(1) of the Electronic Information and Transactions Law. Implications: The findings indicate that the application of the consumer loss element remains legally debatable because the victims are more appropriately categorized as investors than consumers. Highlights: Judicial reasoning established misleading digital information and resulting financial harm but provided limited examination of victim classification. The legal relationship primarily reflected capital placement for profit-seeking activities rather than end-user participation in goods or services. Classification of victims as investors raises questions regarding fulfillment of the statutory requirement concerning consumer losses. Keywords: Fraudulent Investment, ITE Law, Electronic Transactions, Consumer, Telegram